A paranoia e o aparelho de influenciar - Grecco, João Ezequiel (2005)
The proposal of this dissertation seeks to the discussion of the psychosis, and in particular of the paranoia, of psychoanalyst Victor Tausk's point of view, with relationship to the genesis of the " apparel of influencing ". Starting from my clinical case, I established theoretical relationships with this concept. I verified the importance of rescuing the theory of the paranoia proposal for Tausk, as well as, at the present time, I could find facts that suggest manifestation of the apparel of influencing in paranoiac patients. . Finally, I discuss the film A brilliant mind, in order to illustrate with the paranoia lived by a mathematician, winner of the prize Nobel, resembles each other to the apparel of influencing